Antimicrobial and antivirulence efficacies of citral against foodborne pathogen Vibrio parahaemolyticus RIMD2210633. (February 2021) - Cao, Juanjuan; Liu, Huan; Wang, Yi; He, Xiaoxian; Jiang, Heyang; Yao, Jiaojiao; Xia, Fei; Zhao, Yanni; Chen, Xuefeng
Abstract: The emergence of extensive and pandrug resistant Vibrio parahaemolyticus, which is recognized as the leading cause of seafood borne gastroenteritis globally, necessitates the urgent development of novel therapeutic strategies and antibacterial drugs. This study aims to investigate the effects of citral on the growth and virulence properties of V. parahaemolyticus RIMD2210633. Citral displayed good antibacterial activity and the minimum inhibitory concentration (MIC) was determined to be 0.125 mg/mL by two-fold broth dilution method. Citral caused damages to the bacterial cell wall and membrane, based on both the morphology observation by scanning electron microscopy and the elevated glucose content, protein leakage, and malondialdehyde content in the cell cultures. The treatment with citral at subinhibitory concentrations caused the decline in biofilm formation, motility, extracellular polysaccharide production, and also the transcription levels of genes involved in hemolysin production, type III, and VI secretion systems in V. parahaemolyticus RIMD2210633. Also, citral inhibited the quorum sensing genes and ToxRS system in a concentration dependent manner. Furthermore, the citral treated group exhibited a reduced death rate and alleviating infection symptoms of the zebrafish model caused by V. parahaemolyticus RIMD2210633. These results demonstrated that citral may be of interest as alternative therapeutics against V. parahaemolyticus associated infections in seafood. Highlights: Citral displayed good antimicrobial activity against V. parahaemolyticus. . Citral displayed antivirulence activity against V. parahaemolyticus. Citral repressed quorum sensing and ToxRS system of V. parahaemolyticus.